ALIH KODE DALAM TWITTER - Mokodompit, Syuli (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT This article entitles â€œCode Switching on Twitterâ€. The aim of this research are to identify and analyze the code switching appeared in the twitter andÂ explain the reason for the phenomena mentioned above. The data has been collected from Twitter edition January â€“ March 2013, the theory that is used in this research is Dell Hymes theory using descriptive method. The results of this research shows that the code switching due to speakers, partner speech, main point, functions and objectives. According to the function there are two forms in code switching on twitter, they are phrase and sentence. Code switching can occur due to situation deemed inappropriate or irrelevant contextual and situational in the use of two or more language. Keywords : Code Switching, Twitter, speaker, referent, function and objectives, Dell Hymesâ€™s theory.